Circulating Tumor DNA and Hepatocellular Carcinoma - Yang, Ju Dong; Liu, Minetta C.; Kisiel, John B. (Seminars in Liver Disease, 2019)
There is a clear and unmet need for biomarkers in hepatocellular carcinoma (HCC). Circulating cell free deoxyribonucleic acid (cfDNA) is a fragmented DNA subtype, found in the blood circulation. Circulating tumor DNA (ctDNA) is the fraction of total cfDNA, which originates from the primary tumor or metastases in patients with cancer. Earlier studies reported that quantitative measurement cfDNA has diagnostic and prognostic role for HCC. More recently, improvement in next-generation sequencing technology and better understanding of genetic or epigenetic alteration of HCC have allowed comprehensive analysis of mutational and methylation landscape of ctDNA. Hotspot mutation panels and methylation panels have both shown promising performance. None of these tests have yet been validated in longitudinal cohorts for preclinical detection of HCC. In this article, the authors discuss the currently available ctDNA detection technologies, their diagnostic and prognostic performance in HCC, and future research directions.
Keywords: cfDNA; ctDNA; circulating biomarker; liver cancer; cell-free nucleic acids; biomarkers; carcinoma; hepatocellular cancer